Radiological assessment of cup anteversion with a novel 3D-printed highly-porous titanium dual mobility cup - Nicole Puteo; Edoardo Matteo Valentino; Vittorio Davidoni; Domenico Tigani (Journal of Orthopaedic Surgery and Research)
Abstract Background Cup anteversion after primary total hip arthroplasty (THA) with monobloc dual mobility cups (DMC) is difficult to measure on anterior-posterior (AP) pelvic radiographs because of the implant radiopacity and cup design which do not allow for an accurate visualization of the radiographic projection of the cup equatorial rim and the femoral head. This study aims to radiographically investigate on the reliability and accuracy of different measurement methods for cup anteversion in monobloc DMC THA, by comparing a novel titanium cup with conventional cup designs. Methods 97 THAs with a monobloc 3D-printed titanium DMC were radiographically assessed for cup radiographic anteversion (RA) one month postoperatively. RA were measured by three blinded observers through Lewinnek, Woo-Morrey methods and an open access mathematical software (GeoGebra), used as reference method. Intra- and interobserver reliability of RA measurements were evaluated for each method using intraclass correlation coefficient (ICC). Accuracy was assessed comparing Lewinnek and Woo-Morrey methods with GeoGebra. Moreover, further 98 THAs with conventional different brand DMC were radiographically assessed as control group by using the same methods. Results ICC for intra- and interobserver reliability for RA measurements with GeoGebra, Lewinnek and Woo-Morrey methods were 0.975–0.980, 0.978 − 0.965, and 0.979 − 0.958, respectively, for the titanium DMC group. Lewinnek resulted more accurate for RA than Woo-Morrey, differing by + 0.4° (p = 0.06) and + 4.4° (p < 0.001) from GeoGebra, respectively. ICC for intra- and interobserver reliability for GeoGebra, Lewinnek and Woo-Morrey methods were 0.848 − 0.756, 0.843 − 0.801, and 0.965 − 0.958, respectively, for the control DMC group. Lewinnek and Woo-Morrey methods differed by -2.3° and + 5.1° from GeoGebra, respectively (p < 0.001). Conclusions RA measurements are more consistent, repeatable and accurate with a titanium DMC than standard DMC, due to the minor radiopacity of the former cup which enable RA measurements on AP radiographs. Conversely, RA measurements of conventional DMC are more consistent but less accurate if performed on cross-table lateral radiographs by Woo-Morrey method than AP radiographs.